THE ROLE OF COMMUNICATION IN DEVELOPING LEADERSHIP AND TEAMWORK IN SCHOOLS - Wafi Ali Hajjaj; Al Munip; Nurjali (CV. ADIBA AISHA AMIRA, 2024)
Effective communication in an educational environment serves not only as a tool to convey information, but also as a means to inspire, motivate and better coordinate school activities. Through clear and open communication, principals and teachers can ensure each team member understands their goals and tasks, build trust and create a positive and collaborative climate. In addition, good communication also facilitates the process of receiving constructive criticism and sharing innovative ideas that can improve the quality of educational programmes and activities. Conflicts that arise within the team can also be managed wisely through dialogic and open communication approaches, maintaining harmony and keeping the school environment conducive to learning and development. Thus, good communication skills are essential in the development of effective leadership and solid teamwork in schools